Strategy to Develop Traditional Fishery Business in Implementing the Principle of Sustainable Business - Yanfika, Helvi; Amanah, Siti; Fatchiya, Anna; Asngari, Pang S (Jurnal Penyuluhan, 2018)
The importance of sustainable development in fishery has been clearly seen in Indonesia through the existence of Law No.31 Year 2004 on Fishery. It is stated that fishery development is aimed to create job opportunities, fish farmer and fisherman welfare, and to maintain the sustainability of fishery resource and environment. Therefore, all aspects of fishery development activities, including traditional fish processing business should be based on the view of sustainable development. According to the description, the objectives of this study are: (1) to analyze traditional fish processing business; (2) to determine factors influencing one another in sustainable fishery business; and (3) to formulate strategy to improve the competence of traditional processing workers. This research was conducted through the method of survey in three regencies in Lampung Province; namely Tanggamus Regency, Pringsewu Regency, and East Lampung Regency, with a number of samples amounting to 235 respondents; later on the number of samples in each group was determined using the technique of proportional random sampling. Assessment towards the fish processing workers in sustainable traditional processing business generated quite good result since the processing workers were confident that the business developed well and sustainably. The competence of processing workers is influenced by non-formal education and entrepreneurial characteristics. The competence and implementation of extension has a direct influence, while individual characteristics of processing workers indirectly influence the sustainable traditional fishery business. Strategy to improve the competence of sustainable traditional fishery business is done by: (a) strengthening the competence of traditional fish processing workers particularly in technical and managerial aspects through the development of entrepreneurial characteristics; and (b) strengthening the extension intensity through extension method and media to create changes in behavior in running a sustainable traditional fishery business (economy, social, and environment).Keywords: Sustainable, fishery, traditional processing workers, strategy